Formação de leitores na educação infantil: para que contar histórias, professora? - PINHEIRO, Leonice Costa (2019)
The present work of conclusion of the Course of Pedagogy of the Federal University of Pará - PLAN OF ACTIONS ARTICULATED TRAINING OF TEACHERS OF BASIC EDUCATION - PARFOR, has as its title Training of readers in Early Childhood Education: to tell stories, teacher ?, part of the following question : what is the importance given by teachers to storytelling in the training of reading children in the Infant Education of the School in the Infant Education and Early Childhood Covenant Regime Rossi – Castanhal / Pa ?. In view of the issue, it is proposed, as a general objective, to analyze the importance attributed by teachers to the storytelling of the training of reading children in Early Childhood Education at the Cristiana Rossi School in the Municipality of Castanhal. And as specific objectives a) to verify what meaning and meaning the teachers of Early Childhood Education of the Rossi School attribute to the storytelling in their daily practices; b) Identify how and when the storytelling is developed in Early Childhood Education at the Rossi Christian School and c) Unveil the reading education of the teachers of Early Childhood Education at the Cristiana Rossi School. We developed a bibliographical research, field and qualitative approach, where we used interviews with teachers of early childhood education. The results found in this work make it increasingly evident the importance of storytelling in children's education for a training of readers, as well as the teachers have a good reading and reading involvement and then understand literature more as a possibility development and learning.